Side effects and efficacy of low-dose amiodarone in rhythm disorders - Rano Kirkimbayeva; Ayan Abdrakhmanov; Rustam Albayev; Telman Seisembekov; Aizhanа Shaimerdinova (National Scientific Medical Center, 2024)
Amiodarone is one of the most widely used antiarrhythmic drugs, which is the most effective drug for maintaining sinus rhythm. Taking this drug correlates with side effects such as pulmonary toxicity, thyroid dysfunction, neurotoxicity, hepatotoxicity, and skin manifestations. In addition, in some cases, amiodarone remains as a first-line therapy to maintain sinus rhythm. The side effects of amiodarone depend on the dose and duration of the drug. Systematic reviews and meta-analyses have shown the safety profile of a low dose of amiodarone, defined as 200 mg and a very low dose of amiodarone 100 mg. Due to the use of catheter ablation, the use of a low dose of amiodarone is sufficient. In this literature review, we have cited the side effects of a low dose of amiodarone. In addition, although there is evidence of a safer low-dose spectrum, it is not free from side effects and needs to develop an algorithm for early detection of adverse events, as well as studying the effectiveness according to modern research methods, such as an implantable heart monitor, which in turn is of undoubted interest.